Effects of Control Mapping Strategies on Task Performance, Motivation, and Engagement of Participants in a VR Upper Limb Training Task: A Randomized Controlled Trial - Huang, Binhao; Lv, Jian; Qiang, Ligang (Computer animation and virtual worlds, 2025)
ABSTRACT This study explores the use of virtual reality (VR) in upper limb rehabilitation, comparing bionic and non‐bionic control strategies. While VR shows potential for immersive, engaging rehabilitation, recent findings question the effectiveness of prioritizing user rehabilitation needs over bionic strategies. Few studies have examined the impact of these strategies on motor performance, motivation, and engagement. To address this, we designed two hand motion control systems—bionic and non‐bionic—using a virtual block test. The results show that the bionic control strategy improves early training experiences and motor performance, but with practice, the non‐bionic control group demonstrates greater adaptability, motor flexibility, and learning efficiency. This suggests that while bionic strategies may be beneficial in early stages, arbitrary control systems offer better long‐term outcomes.